Ks. Józef Pochwat MS, „Misterium iniquitatis”. Studium tajemnicy nieprawości w dziełach Jana Kasjana (360-435), Kraków 2012, Wydawnictwo La Salette, ss. 384. - Sobiech, Marcin (Vox Patrum, 2012)
nie dotyczy